A Discriminatory Channel Estimation Scheme Based on the Aid of Friendly Jammer - Rong Zhang; Xianzhong Xie; Weijia Lei (Dianxin kexue)
In the physical layer security,that inhibiting the accuracy of channel estimation at eavesdropper can indirectly enhance the received signal quality difference between the legitimate receiver and the eavesdropper,thus improving signal transmission security.The proposed discriminatory channel estimation scheme was based on the help of friendly jammer,which was based on artificial noise emitted by friendly jammer to interfere the channel estimation process of the eavesdropper.Further,the optimal power allocation was given between training sequence and artificial noise by maximizing the channel estimation error of the eavesdropper,which can suppress the channel estimation quality of the eavesdropper more effectively.Simulation results show that this method can effectively restrain the channel estimation performance of the eavesdropper,and it can improve the received signal quality gap between the legitimate receiver and the eavesdropper.